Japan Prosthodontic Society position paper on "occlusal discomfort syndrome". Issue 3 (July 2016) - Tamaki, Katsushi; Ishigaki, Shoichi; Ogawa, Takumi; Oguchi, Hitoshi; Kato, Takafumi; Suganuma, Takeshi; Shimada, Atsushi; Sadamori, Shinsuke; Tsukiyama, Yoshihiro; Nishikawa, Youji; Masumi, Shin-ichi; Yamaguchi, Taihiko; et al.
Abstract: Purpose: Dentists may encounter patients who present with a sense of a malocclusion but in whom no objective findings can be detected. For the patient who insists that there is occlusal discomfort, in the absence of evidence some dentists elect to perform an occlusal adjustment that not only fails to alleviate symptoms, and may, in fact, exacerbate the discomfort. The patient–dentist relationship is then likely compromised because of a lack of trust. Study selection: In 2011, the Clinical Practice Guidelines Committee of the Japan Prosthodontic Society formulated guidelines for the management of occlusal discomfort. When formulating clinical practice guidelines, the committee bases their recommendations on information derived from scientific evidence. For "occlusal dysesthesia, " however, there are an insufficient number of high-quality papers related to the subject. Therefore, a consensus meeting was convened by the Japan Prosthodontic Society to examine evidence in the Japanese- and English-language literature and generate a multi-center survey to create an appropriate appellation for this condition. Results: As a result of the consensus meeting and survey findings, this condition may be justifiably termed "occlusal discomfort syndrome." Conclusions: The Japan Prosthodontics Society believes that identification of an umbrella term for occlusal discomfort might serve as a useful guide to formulating clinical practice guidelines in the future. This position paper represents summary findings in the literature combined with the results of a multicenter survey focused on dental occlusal treatment and the condition of patients who present with occlusal discomfort syndrome.